Microbiological quality assessment of aqueous herbal teas sold in Cotonou, Benin - BABA-MOUSSA, FARID A. KADER; ALLABI, AUREL CONSTANT EUSTACHE; MOUTAIROUMOUTAIROU, KABIROU; ADOUNKPE, M. FERDINAND; KEKE, Martin; Gbegbe, Myrlène (My University, 2017)
The objective of this study was to assess the microbiological quality of herbal teas sold in Cotonou. Thirteen aqueous herbal teas samples were collected from a range of selected sellers located at well- known places. The counting and identification of bacteria and fungi were carried out using International Organization for Standardization microbiological procedures. Chemical and microbiological parameters values were compared to the special norm and quality of drinking water in Republic of Benin. Acidity, pH, Bacteria and moulds were investigated. pH averages values ranged between 8.13±0.34 and 9.91±0.22 and 92% of samples analyzed values did not comply with the National standard of drinking water. Each herbal teas analyzed contained at least one microorganism with a microbial load higher than the national allowed values. The bacteria counting ranged from 9.15±2.32x107 to 3.65±0.87x109 cfu/ml. The fungal counting ranged from 1.6±0.5x104 to 3.5±1.1x106 cfu /ml. Total Coliforms, Escherichia coli, Mesophilic Aerobic Germs, Staphylococcus aureus and Salmonella Typhi load were found in higher values than the acceptable limit, respectively in 54% (n=7), 38% (n=5), 100% (n=13), 46% (n=6) and 15% (n=2) of the tested samples. Among moulds identified, Aspergillus genus was found in all herbal teas with a microbial load which varied between 0.45±0.87x105cfu/ml and 7.30±0.87x105cfu/ml. The study unveiled that herbal teas sold and consumed in Cotonou were contaminated with both bacteria and fungi at various levels inducing a potential risk for the regular consumer arising public health issue. Therefore, proper quality control is needed for herbal teas safety.
Keywords: Herbal teas; medicinal plants; quality issues; safety; microbial contamination